Protocol: Systematic literature review on family business and information and communication technologies - Yadira Robles-Santana; Lidia Sanchez-Ruiz; Raquel Gomez-Lopez (WPOM : Working Papers on Operations Management)
Family businesses move the Spanish economy and are the main job generators in the country, adapting to changes where it is necessary and useful to incorporate Information and Communication Technologies (ICTs) for good business and commercial management. Taking this into consideration, this research aims to carry out a protocol to subsequently develop a systematic literature review on these topics: family businesses and ICTs. This protocol introduces some reflections about the issues of family businesses and ICTs, which gives threads to understand their importance. Likewise, the objective is to give answer to a group of research questions that will be answered along the literature review process. A methodology section is also included. It clearly shows which inclusion and exclusion criteria have been used in the search strategy under the Scopus and Web of Science databases, making visible the total number of scientific articles until reaching a filtered sample of 106 final articles for later review. Finally, a code´s tree is elaborated based on the research questions and a working plan. It ends by including a list of bibliographical references of all the work prior to the development of the protocol.